Triple valvular attack in situs inversus totalis - Silva C, Drs. Gastón; Yajure M, Isaubett (Gaceta Médica de Caracas, 2020)
This clinical case is about a triple valve replacement in a patient with a Situs Inversus Totalis (SIT), intervened at the University Hospital of Caracas, Venezuela, with a satisfactory result. It is a very rare case, and currently few cases were published in the world literature. A mitro-aortic valve replacement with biological valves and implantation of a semi-rigid ring (MC3) in the tricuspid annulus previous valvular plastic was performed under extracorporeal circulation. The result of the surgery was successful with the patient referred to its locality of origin, for definitive cardiological control. Este caso clínico trata sobre un reemplazo de válvula triple, en un paciente con un situs inversus totalis (SIT), intervenido en el Hospital Universitario de Caracas, Venezuela, con un resultado satisfactorio. Es un caso muy raro, actualmente se han publicado en la literatura mundial algunos casos. Se realizó un reemplazo valvular mitro aórtica con válvulas biológicas y la implantación de un anillo semirrígido (MC3) en el anillo tricuspídeo, previa plastia valvular bajo circulación extracorpórea. El resultado de la cirugía fue exitoso con el paciente referido a su localidad de origen, para el control cardiológico definitivo.